Comparison of Cefoxitin and Oxacillin disc diffusion test for the detection of mecA mediated methicillin resistance in Staphylococcus aureus (Bangladesh Journal of Medical Microbiology, 2013)
The study was designed to evaluate the efficacy of cefoxitin disc diffusion test to detect methicillin resistance in Staphylococcus aureus and compare it with oxacillin disc diffusion test and detection of mecA gene by PCR.  A total 116 S. aureus were isolated from clinical samples, collected from SSMC&MH, BIRDEM and NMC hospital, and was isolated by culture and identified by standard laboratory procedure. Antibiotic susceptibility testing was performed by oxacillin (1µg) and cefoxitin (30 µg) discs. PCR for amplification of mecA gene was performed as a gold standard method. Out of 116 isolates, 28 were PCR positive, 33 and 31 were oxacillin and cefoxitin resistant respectively. The sensitivity and specificity for the detection of MRSA was 100% and 94.31%inoxacillin disc diffusion test, and 96.42% and 95.45%in cefoxitin disc diffusion test respectively. Specificity is higher (95.45%) in cefoxitin disc diffusion test than oxacillin disc diffusion test in the detection of MRSA. Use of disc diffusion tests for both oxacillin and cefoxitin can help in more accurate prediction of methicillin resistance than single test, especially in centers which are not equipped to carry out more sophisticated tests for the detection of MRSA.DOI: http://dx.doi.org/10.3329/bjmm.v7i1.19314 Bangladesh J Med Microbiol 2013; 07(01): 7-10